Experimental and numerical studies of axially loaded square concrete‐encased concrete‐filled large‐diameter steel tubular short columns. (18th January 2022) - Ci, Junchang; Kong, Lingxu; Ahmed, Mizan; Liang, Qing Quan; Hamoda, Ahmed; Chen, Shicai; Wu, Chunyu
Abstract: This article presents experimental and numerical studies on the axial compressive behavior of square concrete‐encased concrete‐filled steel tubular (CECFST) short columns composed of a circular inner steel tube. Tests on six full‐scale short CECFST columns with the inner circular tube diameter varying from 320 to 500 mm were carried out to study the influences of sectional diameter and the tube thickness of circular CFST columns on their axial performance. A theoretical model is developed using fiber analysis method and validated against a large test database. The accuracy of various codified design models is evaluated and a simple model is proposed to calculate their ultimate strengths. Test results show that CECFST columns have improved load carrying capacity and can sustain large axial loads without significant strength degradation. In addition, increasing the thickness of the steel tube significantly improves the composite action of the steel and concrete of the inner CFST column, which increases the compressive strength of CECFST columns by 27.3%. However, the rate of increase in the compressive strength of the core concrete of the CFST column has been found to be higher for the column with a smaller local slenderness ratio. The ductility of CECFST columns is influenced by the concrete strength and the spacing of the stirrups. Furthermore, the design model suggested in this study can provide a better estimation than the codified design models.